Employees’ dynamic capabilities-based model of their perceived job security - Bieńkowska, Agnieszka; Tworek, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article concerns the role of employees’ dynamic capabilities in boosting the perceived job security of employees in contemporary organizations. It is assumed that the fit between employees and their job (P-J fit) and employees and their supervisor (P-S fit) in mediating the influence of employees’ dynamic capabilities on perceived job security. Such a theoretical model is empirically verified based on the sample of 1,197 organizations operating in Poland, Italy, and the USA in 2021 when job security was crippled by COVID-19. The results confirm that employees’ dynamic capabilities remain crucial for boosting perceived job security and such relation is mediated by P-J fit and P-S fit.
Keywords: management; employees’ dynamic capabilities; job security